ACTIVATION OF DOMESTIC ALUMINA AND TESTING OF POSSIBILITIES FOR APPLICATION IN SOME MINERAL BASE OILS RAFINATION - Z. R. Petrović; P. T. Dugić; V. M. Aleksić; Lj. C. Vasiljević; T. T. Botić (Journal of Engineering & Processing Management, 2009)
Mineral base oils are extracted from oil fractions of naphta that has boiling point of over 350 ℃, and contain different kinds of carbohydrates and hetero-compunds. Removal of unwanted compunds from mineral base oils in domestic rafineries is made by rafination of imported commercial clays. For ther eventual replacement there has been conducted a testing of various domestic adsorbens. In this paper, examples of natural alumina from the vicinity of Sipovo are previously activated with sulphuric acid, and then used for rafination of naphtenic and hydrocracked base oil in laboratory conditions. Emerged changes on mineral base oils are followed by corresponding standardised methods. Results of testing showed that, by refining the given base oils with activated alumina, one can achieve good results and therefore further explorations shoud be continued, because of their commercial application in semi-industry and industry conditions
Keywords: bauxite; mineral oil